2017
DOI: 10.1002/2017wr020797
|View full text |Cite
|
Sign up to set email alerts
|

Space‐Time Patterns of Meteorological Drought Events in the European Greater Alpine Region Over the Past 210 Years

Abstract: Droughts may have tremendous impacts on humans. However, the space‐time characteristics of droughts are not very well understood, as case studies usually focus on individual drought events. Here we investigate the spatiotemporal drought characteristics of a large sample of events over the past 210 years in the Greater Alpine Region of Central Europe. We use monthly precipitation data, and flag, for each grid point, time steps with precipitation below a 20% percentile. We then propose a new method that detects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Buermann et al (2013) showed that warmer springs going hand in hand with earlier vegetation activity negatively affect soil moisture in summer, and thereby vegetation activity. It is a general observation that warm and dry springs enhance summer temperatures during droughts, which suggests the presence of soil-moisture temperature feedbacks across seasons (Haslinger and Blöschl, 2017). In the case of the Russian heatwave 2010, soil moisture was one of the main drivers (Hauser et al, 2016), hand in hand with persistent atmospheric pressure patterns (Miralles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Buermann et al (2013) showed that warmer springs going hand in hand with earlier vegetation activity negatively affect soil moisture in summer, and thereby vegetation activity. It is a general observation that warm and dry springs enhance summer temperatures during droughts, which suggests the presence of soil-moisture temperature feedbacks across seasons (Haslinger and Blöschl, 2017). In the case of the Russian heatwave 2010, soil moisture was one of the main drivers (Hauser et al, 2016), hand in hand with persistent atmospheric pressure patterns (Miralles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The gridded precipitation data set that they are based on (Efthymiadis et al, 2006) is using station data, which is of course sparse from the beginning of the Note. Mean drought intensity and drought severity are dimensionless measures of space-time precipitation anomalies (see Haslinger & Blöschl, 2017), where drought severity is mean drought intensity times the duration; average precipitation is the observed precipitation averaged over the Greater Alpine Region divided by the duration in days, average precipitation deficit is the average precipitation divided by the climatological mean for the months under consideration; accumulated deficit is the average precipitation deficit times the duration in days.…”
Section: Drought Eventsmentioning
confidence: 99%
“…As pointed out by Mishra and Singh (2010), it is very important to understand historical droughts on regional scales to be able to better assess future drought processes in the wake of global climate change, since drought projections are associated with considerable uncertainty (see Haslinger et al, 2016 for the GAR). Over the last two centuries no trends in meteorological droughts (precipitation deficits) have been observed in the GAR (Haslinger & Blöschl, 2017), although soil moisture droughts have increased due to enhanced potential evapotranspiration associated with increasing temperatures, solar radiation, and vegetation activity (Duethmann & Blöschl, 2018;van der Schrier et al, 2007). The results of this paper suggest that the 1860s are not likely to occur in the near future, as they were closely related to the cool climate at the end of the Little Ice Age around 1850 (Matthews & Briffa, 2005) resulting in strong anomalies of the atmospheric circulation, particularly in MAM.…”
Section: Implications For Understanding Future Climate Changementioning
confidence: 99%
“…Besides regional differences in precipitation characteristics, seasonal patterns exist (Zveryaev, , ) which are typically caused by annual variations of air temperatures, solar insolation, dominant atmospheric weather patterns and vegetation dynamics. On top of that, internal climate variability induces large variations of dry or wet conditions at decadal and inter‐annual timescales (Rimbu et al ., ; Schmidli et al ., ; Casty et al ., ; Pauling et al ., ; Masson and Frei, ; Haslinger and Blöschl, ). Hydro‐meteorological extremes are of particular relevance.…”
Section: Introductionmentioning
confidence: 99%